(untitled) (International journal of artificial intelligence, 2024)
Planning, organizing independent work of students in an informed educational environment and creating all the necessary conditions for this, teaching students to study more during classes, seeing ways to gain knowledge showing, giving a referral for independent work is one of the main tasks of a higher education institution.